Fatores associados com diminuição da sobrevida em 555 transplantes de fígado realizados na Universidade Federal do Ceará - Coelho, Gustavo Rego (2013)
Introduction: Liver transplantation is the only therapeutic option for patients with end-stage liver disease and acute liver failure. Aim: To evaluate the factors that might be associated with decreased graft and patient survival. Methods: All liver transplants performed in the HUWC/FUC from May 18th, 2002 to May 28th, 2011, were analyzed. In this period 555 transplants were performed in 527 patients. Risk factors for graft and patient survival related to characteristics of donors and recipients were analyzed. Results: The mean age of the donors was 34.75 years and the majority were male (68%). The leading cause of death among donors was traumatic brain injury (TBI) (60%). Five hundred and thirty-three (96%) donors had less than 30% steatosis. Fifteen (2.7%) patients had steatosis between 30 and 60%. Only seven (1.3%) patients had steatosis greater than 60%. Patients undergoing liver transplantation had a mean age of 47.35 years. The mean cold ischemia time (CIT) was 350 minutes and warm ischemia time (WIT) was 41 minutes. Most patients were male (73%) and 54.5% Child B and Child C. 38% The calculated MELD score had a mean of 18.55. The prevalence of HCC was 16% and the need for dialysis in the first thirty days after surgery was 10.1%. The retransplant rate was 5.1%. The overall graft survival was 72%, 64%, 60% and 56% and patient survival was 74%, 68%, 64% and 60% at 1, 3, 5 and 10 years. Conclusions: The CIT greater than 600 minutes decreased graft survival in univariate analysis (p <0.05 *). Recipients with fulminant hepatitis had lower survival in univariate analysis (p < 0,05*). Hepatic steatosis greater than 30% and the need for dialysis after transplantation decreased graft and patient survival in univariate and multivariate analysis (p <0.05 *).